2019
DOI: 10.1186/s13068-019-1359-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide increases biofilm formation in Saccharomyces cerevisiae by activating the transcriptional factor Mac1p and thereby regulating the transmembrane protein Ctr1

Abstract: Background Biofilms with immobilized cells encased in extracellular polymeric substance are beneficial for industrial fermentation. Their formation is regulated by various factors, including nitric oxide (NO), which is recognized as a quorum-sensing and signal molecule. The mechanisms by which NO regulates bacterial biofilms have been studied extensively and deeply, but were rarely studied in fungi. In this study, we observed the effects of low concentrations of NO on biofilm formation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Conversely, we propose that Malassezia flavohemoglobins are important for the commensal lifestyle of Malassezia through regulation of NO homeostasis, a hypothesis corroborated by down-regulation of genesencoding putative virulence factors (i.e., allergens and lipases) in our transcriptomic analyses. Another hypothesis is that the HGTmediated acquisition of flavohemoglobins might be important to mediate Malassezia response to NO that is produced by sympatric microbial communities and acts as a quorum signaling molecule, as reported in bacteria (48) and in S. cerevisiae (49).…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, we propose that Malassezia flavohemoglobins are important for the commensal lifestyle of Malassezia through regulation of NO homeostasis, a hypothesis corroborated by down-regulation of genesencoding putative virulence factors (i.e., allergens and lipases) in our transcriptomic analyses. Another hypothesis is that the HGTmediated acquisition of flavohemoglobins might be important to mediate Malassezia response to NO that is produced by sympatric microbial communities and acts as a quorum signaling molecule, as reported in bacteria (48) and in S. cerevisiae (49).…”
Section: Discussionmentioning
confidence: 92%
“…The formation of these biofilms is also potentiated by NO, where transcriptomics together with proteomics revealed the importance of Ctr1p (plasma membrane copper transporter) and its transcriptional regulator Mac1p. This regulation was independent of Flo11p and concentrations of Cu and Fe ions [65] .…”
Section: Model and Natural Biofilmsmentioning
confidence: 80%
“…FLO1 and FLO5 confer cell-cell viscosity and contribute to flocculation ( 30 ). FLO11 encodes a flocculating protein that enhances cell-matrix adhesion and could play a role in development of biofilm in liquid medium ( 31 , 32 ). The results of the qRT-PCR analysis revealed that the expression levels of FLO1 and FLO5 were upregulated in Δ sic1 and Δ cln3 , while the expression of FLO11 was upregulated by 1-fold in Δ sic1 but downregulated by 2-fold in Δ cln3.…”
Section: Discussionmentioning
confidence: 99%
“…Plate-wash assay was to test the ability of invasive growth of different strains. The ability of invasive growth depends on cell-substrate adhesion, which plays a vital role in biofilm formation ( 31 ). In this study, Δ sic1 and Δ cln3 formed more colonies on YPD plates than did WT.…”
Section: Discussionmentioning
confidence: 99%